Evolution of the hadronic system created in relativistic heavy-ion collisions - Anchishkin, D.V.; Muskeyev, A.O.; Vovchenko, V.Yu.; Yezhov, S.N. (Вопросы атомной науки и техники, 2012)
Evolution of the hadronic system in heavy-ion collisions is studied with the reaction density. The three-dimensional reaction zones and their projections for different types of hadronic reactions are calculated for AGS and SPS energies within the microscopic transport model UrQMD. On the basis of performed calculations of reaction frequencies, the characteristic points of the time dependence of fireball evolution are obtained. The hypersurfaces which are the reaction zone boundaries are related to kinetic and chemical freeze-outs. The reaction density fireball representation is compared to other possible representations. Эволюция адронной системы в релятивистских ядро-ядерных столкновениях изучена с помощью плотности реакций. Трехмерная зона реакций, а также ее проекции рассчитаны для энергий AGS и SPS с помощью микроскопической транспортной модели UrQMD. На основе проведенных вычислений частоты адронных реакций получены характерные точки во временной эволюции фаербола. Гиперповерхности, являющиеся границами зон реакций, соотносятся с процессами кинетического и химического фризаутов. Представление фаербола с помощью плотности реакций сравнивается с другими возможными представлениями. Еволюцію адронної системи в релятивістських ядро-ядерних зіткненнях досліджено за допомогою густини реакцій. Тривимірну зону реакцій, а також її проекції розраховано для енергій AGS та SPS за допомогою мікроскопічної транспортної моделі UrQMD. На основі проведених розрахунків частоти адронних реакцій отримані характерні точки у часовій еволюції фаєрбола. Гіперповерхні, що є границями зон реакцій, співвідносяться із процесами кінетичного та хімічного фрізаутів. Представлення фаєрбола за допомогою густини реакцій порівнюється із іншими можливими представленнями.